ONLINE COLLABORATIVE LEARNING: EXPERIENCE IN MONITORING AT THE POST-GRADUATE PROGRAM IN HEALTH SCIENCES. - Ribeiro da Silva, André; de França Barros, Jônatas; França Teles, Lúcio (Journal of Nursing UFPE / Revista de Enfermagem UFPE, 2017)
Objective: reporting the experience as monitor of a semi presential discipline. Method: a descriptive study, experience report about the semi presential monitoring of the on-line discipline << Information production in health on the post graduation course in health science >> of the post graduation program in health science with the Brasília University, and some possible solutions that were exposed by the students during its performance. Results: the low index of evasion and disapproval of the students, the final paper publication in scientific journals perspective and the development of the distance mentoring by all the concluding students were positive results of this analyzes. Conclusion: this discipline monitoring contemplates in a clear and objective way the triad teaching-research-extension, where the student puts his theoretical-practical knowledge in evidence, intensifying the online collaborative learning and the scientific practice production.